Approach of Superior Mesenteric Artery - Lucinschi, Alicia; Matteucci, Pablo (Cirugía del Uruguay, 1980)
Abdominal and thoracoabdominal approaches to the superior mesenteric artery are both valid. The authors describe each procedure in detail and list the advantages of each.